2005
DOI: 10.1002/srin.200505993
|View full text |Cite
|
Sign up to set email alerts
|

Peter Groche

Abstract: Tube hydroforming (THF) is a relatively new but established technology among metal tube forming processes. It is the technology of forming closed sections, hollow parts with different cross‐sections by applying an internal hydraulic pressure and sometimes additional axial compressive loads to force a tubular blank to conform to the shape of a given die cavity. Material properties have a significant influence on the process stability. Often roll‐formed, non‐heat treated tubular materials made of steel with long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The roll forming process is followed by a seam welding station, in which the tubular section is closed using high-frequency induction, laser or tungsten inert gas (TIG) welding processed. A final calibration of the cross-sectional geometry is then conducted, followed by cutting of the tube [12,13]. In addition to the consistency of the wall thickness in the finished tube product, the quality of the weld seam is of critical importance for the subsequent pre-bending and hydroforming process which these tubes will undergo.…”
Section: Tubular Roll Formingmentioning
confidence: 99%
See 1 more Smart Citation
“…The roll forming process is followed by a seam welding station, in which the tubular section is closed using high-frequency induction, laser or tungsten inert gas (TIG) welding processed. A final calibration of the cross-sectional geometry is then conducted, followed by cutting of the tube [12,13]. In addition to the consistency of the wall thickness in the finished tube product, the quality of the weld seam is of critical importance for the subsequent pre-bending and hydroforming process which these tubes will undergo.…”
Section: Tubular Roll Formingmentioning
confidence: 99%
“…In addition to the consistency of the wall thickness in the finished tube product, the quality of the weld seam is of critical importance for the subsequent pre-bending and hydroforming process which these tubes will undergo. Although they do not specify the welding process used, Groche et al [12] showed that continuous roll forming resulted in a weld seam thickness that is greater than the average cross-sectional thickness of the tube due to the force applied to the edges of the sheet during welding. This results in base metal failure when the tubes were subject to free-expansion bulge tests.…”
Section: Tubular Roll Formingmentioning
confidence: 99%